Correlation Between Aphasia in Stroke Patients and Severe Depression of Family Members as Primary Caregivers. - Gunawan, Pricilla Yani; Iswara, Kalista Ardelia (Medicinus, 2021)
Background and Objective: Stroke is a disease with an increasing annual prevalence. One of the most frequent clinical manifestation seen in stroke patients is aphasia which greatly affects the patient’s ability to communicate. The burden and the pressure of taking care of the patient placed on the family members often results in psychological impacts such as depression.  We intend to know the association between aphasia in stroke patients with severe depression on family members. Methodology: This was a cross sectional study, using an unpaired categorical comparative analysis. Inclusion criteria were family members of patients with and without aphasia. Patients and caregivers who gave their consent verbally were guided to fill in the Hamilton Depression Rating Scale questionnaire. The association between aphasia status and the depression scale was analyzed using Chi-Square.Results:  Out of 54 respondents included in the study, there were 25 caregivers (46,3%) taking care stroke patients without aphasia, and 29 caregivers (53,7) taking care stroke patients with aphasia. As much as35 (64.8%) were categorized as normal- moderate level of depression and 19 (35.2%) categorized as major depression. From those with major depression, 14 (73.7%) were found in the aphasic group and 5 were in the non-aphasia group. Chi-Square analysis shows a significant correlation [P=0.03; OR=3.73 (1.1-12.7)] between aphasia in stroke patients and severe depression of the caregivers.Conclusion: There is a significant association between aphasia in stroke patients and the incidence of severe depression on their caregivers.